(untitled) (Journal of Information and Communication Technology, 2023)
Multi-label classification is a unique challenge in machine learning designed for two targets with each containing one or multiple classes. This problem can be resolved using several methods, including the classification of the targets individually or simultaneously. However, most models cannot classify the target simultaneously, and this is not expected to happen in the modeling rule. This study was conducted to propose a novel solution in the form of a Vector Generalized Additive Model Using Cross-Validation (VGAMCV) to address these problems. The proposed method leverages the Vector Generalized Additive Model (VGAM), which is a semi-parametric model combining both parametric and non-parametric components as the underlying base model. Cross-validation was also applied to tune the parameters to optimize the performance of the method. Moreover, the methodology of VGAMCV was compared with a tree-based model, Random Forest, commonly used in multi-label classification to evaluate its effectiveness based on fourteen metric scores. The results showed positive outcomes as indicated by 0.703 average accuracy and 0.601 Area Under Curve (AUC) recorded, but these improvements were not statistically significant. Meanwhile, the method offered a viable alternative for multi-label classification tasks, and its introduction served as a contribution to the expanding repertoire of methods available for this purpose.